PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPERCAYAAN PASIEN PADA RUMAH SAKIT ANNISA MEDIKA 2 PEKANBARU - Annisa Shofiana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to find out how the influence of promotion (advertising. Sales promotion, and public relations) and service quality (Tangibles, Empathy, Reliability, Responsiveness and Assurance) on patient trust (Ability, Benevolence and Integrity) at Annisa Medika 2 Hospital Pekanbaru.The population in this study were patients who visited Annisa Medika 2 Pekanbaru Hospital. With 100 samples, sampling uses the Slovin formula. The research data collection is in the form of primary data, with questionnaires as research instruments and secondary data in the form of company archives, the dta analysis used is using multiple linear regression, determination test, t test and f test with the help of the SPSS program. From the results of data analysis which includes tests of validity, rebility, and multiple linear regression, the results of the t test show the calculation of t count (9.653)> t table (1,984) and sig. (0,000) <0,05. This means that the Promotion variable has a significant effect on Patient Trust. And the results of the study indicate the calculation of t arithmetic (8.995)> t table (1,984) and sig. (0,000) <0.05. This means that the Service Quality variable has a significant effect on Patient Trust and based on the simultaneous test it is concluded that promotion and service quality together have a significant effect on patient trust with a large influence of 56.6% at Annisa Medika 2 Hospital Pekanbaru.Keywords: Promotion, Service Quality, Patient Trust